Perioperative outcomes after open radical cystectomy for muscle invasive bladder cancer - Shrestha, Samir; Maskey, Pukar; Phuyal, Anjit; Shah, Jay N. (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Radical cystectomy with bilateral pelvic lymphadenectomy is a primary intervention for muscle invasive or refractory, high grade Ta, T1, Tis bladder cancer. Owing to its major undertaking, patient succumbs to infection and various morbidities. This study was to assess the perioperative outcomes and complications of radical cystectomy. Methods: This retrospective study analyzed the perioperative outcome (early mortality within 30 days, length of stay, requirement of blood transfusion) of radical cystectomy in patients with bladder cancer during four years at Patan Hospital, Patan Academy of Health Sciences, Lalitpur, Nepal. Ethical approval was obtained. Study variables included patient’s demographics, presenting symptoms, tumor types and configuration, need for blood transfusion, length of surgery, pathological stages, types of urinary diversions, hospital stay, early (<30 days) and late (31-90 days) morbidity and mortality. Results: Total 32 patients underwent radical cystectomy. Data analysed on 18 patients, mean age was 66.7 years and painless hematuria 17 (94.4%). All were transitional cell carcinoma, high grade lesion in 17 (94.4%). Overall 6 (33.3%) patients developed early postoperative complications, paralytic ileus and prolong lymph drainage in 5 (27.8%), wound dehiscence in 4 (22.2%) and ureteric catheter dislodgement in two. There were 2 (11.1% of 18) mortalities (the mortality audit showed total 5 (15.6%) out of 32 radical cystectomy during the study period. Conclusions: Perioperative complications occurred in 1/3rd following radical cystectomy for muscle invasive bladder, more complications in those with preoperative associated co-morbidities.